Organ-specific LPS-induced inflammatory gene expression in adult Zebrafish - Yi. Ma; A. V. Fedorov; K. A. Kondratov; A. A. Knyazeva; M. L. Vasyutina; A. S. Golovkin (Медицинская иммунология, 2021)
Systemic inflammation is known to be a key component of infection and non-infection diseases progression and may lead to multiorgan failure, persistent inflammation, immunosuppression, catabolism syndrome or even indolent death. This importance dictates the need for relevant in vivo models of inflammation to investigate the pathogenesis of numerous diseases and to perform drug screening. Danio rerio (zebrafish) became one of the most important models to explore biological processes in vivo. The aim of the study was to generate a lipopolysaccharide (LPS) model of systemic inflammation in vivo using zebrafish and to identify organspecific proinflammatory genes activity after intraperitoneal LPS infusion. We performed organ specific analysis of main proinflammatory genes expression in zebrafish after LPS stimulation. Comparing 18s, eef1a1l1, gapdh, and actb as potential housekeeping genes, we came to conclusion that eef1a1l1 with 99% effectiveness is the most promising for further normalization in this model. The genes activity was the most pronounced in the heart where the expression of IL6, CXCL8a, and CXCL18β was increased up to 100-fold. Moreover, the kidneys were the most involved in the inflammatory process since the highest number of analysed genes were up-regulated there: expression levels of CXCL18β, CXCL8a, IL1β, IL6, Mpeg1.2, and TNFa were significantly increased. This was probably related to the kidney activity as an immune and hematopoietic organ. The lowest reactivity was detected in the muscles. Immune reactions could be dose-dependent, for instance the infusion of 20 µg LPS led to decrease of expression of IFNy, Mpeg 1.2, and Mpeg 1.1 in the liver and to increase of Mpeg 1.2 expression in the kidney comparing with 10 µg dosage. Thus, due to the high degree of the similarity and other unique properties, Danio rerio has the advantage of being relevant model of inflammation. Our model demonstrated that the investigation of isolated zebrafish organs could be useful and informative for the investigation of inflammatory processes.